MEDICAL AND PSYCHOLOGICAL ASPECTS OF INFERTILITY - S. V. Apresyan; A. A. Abashidze; V. F. Arakelyan (IRBIS LLC, 2016)
Healthy family is an objective criterion of population health and an assessment indicator of social and economic problems. The fraction of infertile couples in Russian Federation varies between 8% and 17% and currently demonstrates no clear trend towards declining. From a social welfare perspective it has not only physical,  familial or psychological repercussions but also social and demographic consequences.